2020
DOI: 10.3390/ani10101930
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin and Naringenin Provide Functional and Antioxidant Protection to Stored Boar Semen

Abstract: In this study, we evaluated the impact of 5–50 μM quercetin (QUE) and naringenin (NAR) on extended boar spermatozoa in the BTS (Beltsville Thawing Solution) medium for 72 h. Spermatozoa motion, membrane, acrosome, and DNA integrity were investigated immediately after sample dilution (0 h) as well as after 24 h, 48 h, and 72 h of semen storage. Furthermore, reactive oxygen species (ROS) and superoxide production, as well as the extent of oxidative damage to the sperm proteins and lipids, were assessed to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 51 publications
2
29
0
Order By: Relevance
“…This could be easily related to the ameliorative effects of L. sativum extract on glutamate-induced DNA damage, cell viability, and the antioxidant effects or scavenging activity. This is in good agreement with two recent studies which demonstrated that quercetin and nariginin were shown to induce mitochondrial activity, significant membrane stabilization, and prevention of lipid peroxidation of treated cells [ 40 , 41 ]. Table 2 demonstrates the richness of L. sativum with tannins, flavonoids, alkaloids, and anthraquinones as phytochemical with well-documented therapeutic potency.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This could be easily related to the ameliorative effects of L. sativum extract on glutamate-induced DNA damage, cell viability, and the antioxidant effects or scavenging activity. This is in good agreement with two recent studies which demonstrated that quercetin and nariginin were shown to induce mitochondrial activity, significant membrane stabilization, and prevention of lipid peroxidation of treated cells [ 40 , 41 ]. Table 2 demonstrates the richness of L. sativum with tannins, flavonoids, alkaloids, and anthraquinones as phytochemical with well-documented therapeutic potency.…”
Section: Discussionsupporting
confidence: 92%
“…The antioxidant effects of L. sativum are shown in Table 6 . This could be attributed to the multiple antioxidant compounds recorded in this plant ( Tables 1 and 2 ) which demonstrate high scavenging power of lipid peroxides and ROS [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…According to Diao et al [ 79 ], 10 μmol/L QUE could significantly improve the motion behavior of spermatozoa collected from leukocytospermic patients. In vitro studies on animal spermatozoa also agree that exposure of male gametes to particularly QUE concentrations ranging between 10 and 25 μmol/L may lead to a higher preservation of motility in bovine [ 80 ] and boar spermatozoa [ 81 , 82 ]. Furthermore, pivotal experiments on cryopreserved boar [ 83 ], stallion [ 84 ], red fowl [ 85 ] and ram [ 86 ] spermatozoa suggest that low QUE concentrations administered to the freezing and thawing medium improve the sperm motility and a subsequent fertilization potential.…”
Section: Quercetinmentioning
confidence: 91%
“…Recent in vitro studies indicate that QUE is a highly efficient biomolecule in preventing the loss of the mitochondrial membrane potential [ 81 ] and a subsequent mitochondrial dysfunction by its ability to accumulate inside the mitochondria [ 90 ] and to control ROS production by its antioxidant activity [ 87 ]. The mitochondrial system is considered to be the primary source of intracellular ROS, whereas QUE may play important roles in the absorption and neutralization of ROS created mainly by the activity of NADPH oxidase and NADH-dependent oxidoreductase, localized in the inner mitochondrial membranes [ 65 , 66 , 91 ].…”
Section: Quercetinmentioning
confidence: 99%
“…Similar to QRC, naringenin (NRG, 2,3-dihydro-5,7-dihydroxy-2-(4-hydroxyphenyl)-4 H -1-benzopyran-4-one) is a natural flavonoid belonging to flavanones, commonly available in tomatoes, bergamot, and citrus fruits that merit further attention [ 21 ]. In particular, recent experiments carried out on boar semen [ 22 ] found that NRG was more effective against lipid peroxidation, while QRC acted as a stronger protective agent against protein oxidation.…”
Section: Introductionmentioning
confidence: 99%